2019
DOI: 10.3390/e21020114
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Room Temperature Mechanical Properties of Different 3 and 4 Element Medium Entropy Alloys from HfNbTaTiZr System

Abstract: Refractory high entropy alloys (HEA) are promising materials for high temperature applications. This work presents investigations of the room temperature tensile mechanical properties of selected 3 and 4 elements medium entropy alloys (MEA) derived from the HfNbTaTiZr system. Tensile testing was combined with fractographic and microstructure analysis, using scanning electron microscope (SEM), wavelength dispersive spectroscope (WDS) and X-Ray powder diffraction (XRD). The 5 element HEA alloy HfNbTaTiZr exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…With changing the alloy √ Table 2 Values of coefficients obtained after fitting the proposed polynomial to the experimental dataset in Table 1 Coefficient The hardest alloy in the Hf-Mo-Nb-Ta-Ti-V-Zr system within the investigated composition range is predicted to be Hf 15 Mo 20 Nb 5 Ta 15 Ti 5 V 20 Zr 20 with the yield stress of 1792 MPa. According to the tensile-ductility data in previous research works [34,[41][42][43][44][45][46][47][48][49][50][51][52], alloys with tensile yield stresses less than 1200 MPa could have tensile ductility higher than 5% (Fig. 8).…”
Section: Alloy Designmentioning
confidence: 99%
See 1 more Smart Citation
“…With changing the alloy √ Table 2 Values of coefficients obtained after fitting the proposed polynomial to the experimental dataset in Table 1 Coefficient The hardest alloy in the Hf-Mo-Nb-Ta-Ti-V-Zr system within the investigated composition range is predicted to be Hf 15 Mo 20 Nb 5 Ta 15 Ti 5 V 20 Zr 20 with the yield stress of 1792 MPa. According to the tensile-ductility data in previous research works [34,[41][42][43][44][45][46][47][48][49][50][51][52], alloys with tensile yield stresses less than 1200 MPa could have tensile ductility higher than 5% (Fig. 8).…”
Section: Alloy Designmentioning
confidence: 99%
“…Tensile ductility versus tensile yield stress for single-phase bcc RHEs[34,[41][42][43][44][45][46][47][48][49][50][51][52] …”
mentioning
confidence: 99%
“…From the study of β-Ti alloys, it is known that oxygen can significantly increase the tensile strength and change the deformation mechanisms [63]. Also, the hardness of hot deformed (without residual porosity) specimens showed significantly higher hardness values (i.e., 450 HV10) than the hardness of arc melted HfNbTaTiZr specimens, which is reported to be 300-350 HV10 [19,44,45,64]. This difference can be ascribed to the strengthening effect of oxygen (interstitial strengthening).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few works using the powder metallurgy process for the synthesis of HfNbTATiZr (or similar) HEAs have been reported to date (e.g., [9,43]). Our previous works reported on the preparation of the HfNbTaTiZr equimolar alloy via the arc melting [44][45][46] and SPS [47] processes. However, the disadvantage of the SPS technology is complicated powder preparation.…”
Section: Introductionmentioning
confidence: 99%
“…The Hf-Nb-Ta-Ti-Zr refractory HEA shows great high-temperature properties and room-temperature properties. Zýka et al [ 44 ] presented investigations of the room-temperature tensile mechanical properties of selected three- and four-element medium entropy alloys derived from the Hf-Nb-Ta-Ti-Zr system, and they found that it is the five-element HEA alloy that exhibits the best combination of strength and elongation. Tseng et al [ 45 ] aimed to reveal the effects of Mo, Nb, Ta, Ti, and Zr on mechanical properties of equiatomic Hf-Mo-Nb-Ta-Ti-Zr alloys.…”
Section: Mechanical Behaviorsmentioning
confidence: 99%